The Role of Forward Rolls in the Development of Gross Motor Skills of Elementary School Students - Alya Rahmawati; Ayudia, Trisa; Riyadi, Afrizal; Yuliansah, Latif; Anugrah, Rano Arvana; Adrian, Rio; Wahyudi, Aldi; Ramadhan, Daffa Fadlamsyah; Destriansyah, Yuki; Fauzi, Rizal Ahmad (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
Gross motor development is one of the crucial elements in the growth and development of elementary school children. One type of physical activity that can support this progress is the forward roll movement in floor gymnastics. This study aims to understand the role of forward roll training in improving students' gross motor skills in elementary schools. The method used is qualitative research with a case study approach, involving two physical education teachers at an elementary school in Sumedang Regency. Data were collected through interviews, observations, and documentation. The research findings indicate that forward roll movements are very effective in improving large muscle strength (core, arms, legs), body coordination, and balance. Teachers apply gradual and flexible strategies according to students' physical abilities, and combine character and cross-disciplinary values ​​in the learning process. Indicators of successful gross motor development include improving movement techniques, courage to try, and enthusiasm in practicing. The main obstacles in forward roll training are students' fear and limited equipment, which are overcome by playing methods and using existing tools. These findings confirm the significance of optimizing forward roll training as a component in physical education teaching strategies in elementary schools.